Advances in Dental Care: Emerging Technologies, Patient Safety, and Quality Outcomes - ALNASSAR, ETETHAR ALI; ALJEAN, FATMAH AMER J; ALHAFI, MASHAEL SANAD B; ALOTAIBI, EMAN OMAIR; ALBRAHIM, AYAT HUSSAIN; ALHARBI, ABEER NAIF; ALQARNI, FATIMAH MOHAMMED; ALIBRAHIM, KHULOOD IBRAHIM; ALBRAHIM, REHAB MOHSIN (Journal of Posthumanism, 2024)
Lifelong learning through CE also addresses emerging societal needs in dentistry. Topics such as sustainability, digital ethics, and patient safety culture are increasingly featured in CE curricula. Addressing these issues ensures that dentistry evolves in alignment with broader healthcare and societal expectations. By engaging with contemporary themes, dental professionals remain relevant and responsive to changing patient demands, reinforcing dentistry’s role as a progressive and adaptive field.